Thermoplastic resin composition and method for producing same

By adding a specific amount of lubricant to the rubber reinforced styrene resin powder, the problems of poor dispersion and fluidity of rubber polymers are solved, and the balance of high impact strength, fluidity and thermal stability is achieved, which is suitable for a variety of application scenarios.

JP7628044B2Active Publication Date: 2025-02-07NIPPON A & L INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021054725
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-02-07
Estimated Expiration
2041-03-29

AI Technical Summary

Technical Problem

In the prior art, the rubber polymer dispersion and poor fluidity caused by increasing the proportion of rubber polymers are reduced, making it difficult to improve fluidity and thermal stability while maintaining high impact strength and surface appearance.

Method used

By adding a specific amount of lubricant to the rubber-reinforced styrene resin powder, it ensures that it has a melt volume ratio of at least 20 cm³/10 minutes after mixing, and meets the proportional relationship of 5≦X/Y≦250, where X is the melt volume ratio and Y is the lubricant content, achieving good fluidity and surface appearance.

Benefits of technology

The high impact strength, fluidity and thermal stability of rubber-enhanced styrene resin are achieved, and are suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628044000001
    Figure 0007628044000001
Patent Text Reader

Abstract

To provide a thermoplastic resin composition that has all of impact resistance, flowability, heat resistance and a good surface appearance in a balanced manner, and a method for producing the same.SOLUTION: A thermoplastic resin composition contains rubber-reinforced styrenic resin powder containing a lubricant of 0.2 pts.mass or more, with a melt volume rate (220°C, 10 kg) of 20 (cm3 / 10 min) or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition having an excellent balance of impact resistance, fluidity, heat resistance and surface appearance, and a method for producing the same. [Background technology]

[0002] Rubber-reinforced styrene resins, such as ABS resin, are excellent in impact resistance, moldability, and surface appearance, and are used in various fields such as vehicle parts and electrical products. In rubber-reinforced styrene resins, graft polymers formed by graft polymerization of styrene monomers are dispersed in rubber polymers, and it is known that the state of dispersion affects impact resistance and surface appearance. In order to improve productivity, economic efficiency, and freedom of component design of final compositions containing rubber-reinforced styrene resins, there is a tendency to increase the proportion of rubber polymers in the graft polymers. However, if the proportion of rubber polymers in the graft polymers is increased, the dispersibility of the rubber polymers decreases when the graft polymers are melt-kneaded with other resins, resulting in decreased impact resistance and surface appearance. Therefore, Patent Document 1 proposes that the above problem can be improved by using the melt viscosity a (Pa·s) of the graft polymer (A), the melt viscosity b (Pa·s) of the polymer (B), and the content ratio x (wt%) of the rubber polymer in the graft polymer (A) to satisfy (Formula 1) a / (b·x)≦0.7 in a thermoplastic resin composition consisting of a graft polymer (A) and a polymer (B). However, when the content ratio x of the rubber polymer in the graft polymer (A) is increased, the melt viscosity a of the graft polymer (A) inevitably increases, and in order to satisfy (Formula 1), it is necessary to increase the melt viscosity b of the polymer (B). This leads to a decrease in the fluidity of the thermoplastic resin composition consisting of the graft polymer (A) and the polymer (B). Therefore, when the content ratio of the rubber polymer in the graft polymer is increased, the dispersibility of the rubber polymer and the fluidity of the thermoplastic resin composition are in a trade-off relationship, and the material that combines these properties is not yet satisfactory. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-273578 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a thermoplastic resin composition having an excellent balance of impact resistance, fluidity, heat resistance and surface appearance, and a method for producing the same. [Means for solving the problem]

[0005] As a result of intensive research, the inventors of the present invention found that the melt volume rate (220°C, 10 kg) was 20 (cm 3 The inventors have found that, with respect to a thermoplastic resin composition containing a rubber-reinforced styrene-based resin powder having a viscosity of 100 / 10 minutes or more, the above-mentioned problems can be solved by adding a specific amount of a lubricant to the rubber-reinforced styrene-based resin powder, and have thus completed the present invention.

[0006] That is, the present invention comprises the following [1] to [4]. [1] A thermoplastic resin composition containing a rubber-reinforced styrene-based resin powder, which satisfies the following conditions (1) and (2): (1) The rubber-reinforced styrene-based resin powder contains 0.2 parts by mass or more of a lubricant per 100 parts by mass of the rubber-reinforced styrene-based resin component. (2) The melt volume rate (220°C, 10 kg) of the thermoplastic resin composition is 20 (cm 3 / 10 minutes) or more. [2] The thermoplastic resin composition according to claim 1, further satisfying the following condition (3): (3) The following formula (i) is satisfied: 5≦X / Y≦250... formula (i) X: Melt volume rate of thermoplastic resin composition (220°C, 10 kg) Y: Lubricant content of rubber-reinforced styrene-based resin powder [3] A compound obtained by mixing 0.2 parts by mass or more (solid content equivalent) of an emulsion-state lubricant with 100 parts by mass (solid content equivalent) of rubber-reinforced styrene-based resin latex and then powdering the rubber-reinforced styrene-based resin powder into a mixture, the melt volume rate (220°C, 10 kg) of which is 20 (cm 3 / 10 minutes) or more. [4] The method for producing a thermoplastic resin composition according to claim 3, further characterized in that the following formula (i) is satisfied: 5≦X / Y≦250... formula (i) X: Melt volume rate of thermoplastic resin composition (220°C, 10 kg) Y: Lubricant content of rubber-reinforced styrene-based resin powder Effect of the Invention

[0007] According to the present invention, it is possible to provide a thermoplastic resin composition having an excellent balance of impact resistance, fluidity, heat resistance and surface appearance, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below.

[0009] The thermoplastic resin composition of the present invention contains a rubber-reinforced styrene-based resin powder.

[0010] The rubber-reinforced styrene-based resin powder of the present invention is obtained by powdering a rubber-reinforced styrene-based resin latex containing a latex of a graft copolymer (A) essentially containing a styrene-based monomer component obtained by an emulsion polymerization method, or a latex mixture of a latex of the graft copolymer (A) and a polymer (B) containing a vinyl-based monomer component obtained by an emulsion polymerization method.

[0011] The graft copolymer (A) is obtained by graft polymerization of a rubber polymer and a monomer containing a styrene-based monomer.

[0012] The rubbery polymer constituting the graft copolymer (A) is not particularly limited, and includes conjugated diene rubbers such as polybutadiene rubber, styrene-butadiene rubber (SBR), and acrylonitrile-butadiene rubber (NBR); ethylene-propylene rubbers such as ethylene-propylene-non-conjugated diene (ethylidene norbornene, dicyclopentadiene, etc.) rubber; acrylic rubbers such as polybutyl acrylate rubber; and silicone rubbers, and can be used alone or in combination, or can be used as a rubbery polymer having a multilayer structure. Among them, it is preferable to include a conjugated diene rubber from the viewpoint of impact resistance.

[0013] The mass average particle diameter of the rubber polymer is not particularly limited, but is preferably 50 to 1000 nm, more preferably 200 to 800 nm, and even more preferably 300 to 500 nm. By adjusting the diameter within the above range, the balance between mechanical strength and surface appearance tends to be excellent.

[0014] The monomer capable of being graft polymerized onto the rubber polymer of the graft copolymer (A) essentially comprises a styrene-based monomer such as styrene or α-methylstyrene, and further includes vinyl cyanide-based monomers, (meth)acrylic acid ester-based monomers, maleimide-based monomers, amide-based monomers, unsaturated carboxylic acid-based monomers, polyfunctional monomers, etc., and one or more of these can be used.

[0015] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, ethacrylonitrile, and fumaronitrile.

[0016] Examples of the (meth)acrylic acid ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl acrylate, phenyl (meth)acrylate, 4-t-butylphenyl (meth)acrylate, (di)bromophenyl (meth)acrylate, and chlorophenyl (meth)acrylate.

[0017] Examples of the maleimide monomer include N-phenylmaleimide and N-cyclohexylmaleimide.

[0018] Examples of the amide monomer include acrylamide and methacrylamide.

[0019] Examples of the unsaturated carboxylic acid monomer include (meth)acrylic acid, ethacrylic acid, maleic acid, fumaric acid, itaconic acid, and crotonic acid.

[0020] Examples of the polyfunctional monomer include divinylbenzene, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, diallyl phthalate, dicyclopentadiene di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol hexa(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, triallyl cyanurate, and triallyl isocyanurate.

[0021] The content of the rubber polymer in the graft copolymer (A) is not particularly limited, but is preferably 20 to 80% by mass, more preferably 40 to 70% by mass. By adjusting the content within the above range, the balance between mechanical strength and surface appearance tends to be excellent.

[0022] The graft ratio of the graft copolymer (A) and the reduced viscosity of the acetone soluble portion are not particularly limited, but the graft ratio is preferably 20 to 150%, more preferably 30 to 100%, and even more preferably 36 to 75%. The reduced viscosity of the acetone soluble portion is preferably 0.2 to 1.5 dl / g, and more preferably 0.3 to 1.0 dl / g. By adjusting the ratio within the above range, the balance between mechanical strength and fluidity tends to be excellent.

[0023] The graft ratio and the reduced viscosity of the acetone soluble matter can be determined as follows.

[0024] Separation method Approximately 2 g of graft copolymer (A) and 60 ml of acetone were placed in an Erlenmeyer flask and left to soak for 24 hours. The mixture was then centrifuged at 15,000 rpm for 30 minutes in a centrifuge to separate the soluble and insoluble portions. The insoluble portion was obtained by drying overnight at room temperature using a vacuum dryer. The soluble portion was obtained by precipitating the acetone-soluble portion in methanol and drying overnight at room temperature using a vacuum dryer. Grafting rate Graft rate (%) = (X-Y) / Y x 100 X: Amount of acetone insoluble matter after vacuum drying (g) Y: Amount of rubber polymer in graft copolymer (A) (g) Reduced viscosity of acetone soluble matter (dl / g) The acetone soluble portion is dissolved in N,N-dimethylformamide to give a solution with a concentration of 0.4 g / 100 ml, and the reduced viscosity is calculated from the flow time measured at 30°C using a Cannon-Fenske type viscometer.

[0025] The polymer (B) is a polymer obtained by polymerizing monomers including a vinyl monomer.

[0026] Examples of the vinyl monomer include styrene monomers, vinyl cyanide monomers, (meth)acrylic acid ester monomers, maleimide monomers, amide monomers, unsaturated carboxylic acid monomers, polyfunctional monomers, etc., and one or more of these monomers can be used. As each monomer, the above-mentioned monomers can be used.

[0027] The reduced viscosity of the polymer (B) is not particularly limited, but is preferably 0.2 to 1.5 dl / g, and more preferably 0.3 to 1.0 dl / g. By adjusting the reduced viscosity within the above range, the balance between mechanical strength and fluidity tends to be excellent.

[0028] The reduced viscosity can be calculated by the following formula.

[0029] The polymer (B) is dissolved in N,N-dimethylformamide to give a solution having a concentration of 0.4 g / 100 ml, and the reduced viscosity is determined from the flow time measured at 30° C. using a Cannon-Fenske type viscometer.

[0030] The above rubber polymer, graft copolymer (A) and polymer (B) can be obtained by a known emulsion polymerization method.

[0031] Examples of emulsifiers used in emulsion polymerization include aliphatic carboxylates such as potassium oleate, dipotassium alkenylsuccinate, and sodium rosinate; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate; aliphatic sulfonates such as sodium lauryl sulfate; alkyldiphenylether disulfonates; sulfate ester salts of higher alcohols; formalin condensates of naphthalenesulfonic acid; anionic surfactants such as sulfate ester salts of nonionic surfactants; and nonionic surfactants such as alkyl ester type, alkylphenyl ether type, and alkyl ether type of polyethylene glycol. One or more of these may be used.

[0032] Examples of initiators used in the emulsion polymerization method include persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate; redox type initiators using sodium sulfite, sodium thiosulfate, sodium formaldehyde sulfoxylate, ascorbic acid, ferrous sulfate, or the like as a reducing agent, and potassium peroxodisulfate, hydrogen peroxide, benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, acetyl peroxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, or the like as an oxidizing agent.

[0033] The rubber polymer content of the rubber-reinforced styrene-based resin powder of the present invention is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more. By adjusting it to the above range, the degree of freedom in component design of the final composition containing the rubber-reinforced styrene-based resin powder can be improved.

[0034] The rubber polymer content of the rubber-reinforced styrene-based resin powder can be adjusted by adjusting the content of the rubber polymer constituting the graft copolymer (A) or by mixing the graft copolymer (A) and the polymer (B) in a latex state.

[0035] The rubber-reinforced styrene-based resin powder of the present invention can be obtained by powdering a rubber-reinforced styrene-based resin latex containing a latex of the graft copolymer (A) or a latex mixture of the latex of the graft copolymer (A) and the latex of the polymer (B).

[0036] Examples of methods for powdering include a spray-drying method and a wet method in which a coagulant is added to coagulate into a slurry state.

[0037] Examples of coagulants used in the wet method include inorganic acids such as hydrochloric acid, phosphoric acid, sulfuric acid, and nitric acid, organic acids such as formic acid and acetic acid, and inorganic acid metal salts such as magnesium sulfate, calcium chloride, and aluminum sulfate. These can be used alone or in combination.

[0038] After solidification, the mixture is washed with water, dehydrated, and dried to obtain a rubber-reinforced styrene-based resin powder.

[0039] The rubber-reinforced styrene-based resin powder of the present invention contains 0.2 parts by mass or more, and preferably 0.3 parts by mass or more, of a lubricant per 100 parts by mass of the rubber-reinforced styrene-based resin component (graft copolymer (A), or graft copolymer (A) and polymer (B)). By adjusting the amount of the lubricant within the above range, the surface appearance tends to be excellent. The content of the lubricant refers to the amount added before the rubber-reinforced styrene-based resin is powdered, and does not include, for example, the amount of the lubricant added during melt-kneading.

[0040] Examples of the lubricant include hydrocarbon-based lubricants such as low molecular weight wax, paraffin wax, polyethylene wax, chlorinated hydrocarbons, and fluorocarbons; natural wax-based lubricants such as carnauba wax and candy wax; fatty acid-based lubricants such as higher fatty acids such as lauric acid, stearic acid, and behenic acid, and oxyfatty acids such as hydroxystearic acid; fatty amide-based lubricants such as stearylamide, laurylamide, and oleylamide; and alkylene bis-aliphatic amide compounds such as methylene bis-stearylamide and ethylene bis-stearic acid amide; ester compounds of fatty acids and monohydric alcohols such as stearyl stearate, butyl stearate, and distearyl phthalate; Examples of the lubricant include fatty acid alcohol ester lubricants such as ester compounds of fatty acids and polyhydric alcohols, such as rhythritol tetrastearate, dipentaerythritol hexastearate, polyglycerol polyricinoleate, and hydrogenated castor oil; complex ester compounds of monovalent fatty acids and polybasic organic acids and polyhydric alcohols, such as dipentaerythritol adipic acid-stearic acid ester; fatty acid alcohol lubricants such as stearyl alcohol, lauryl alcohol, and palmityl alcohol; metal soaps of fatty alcohols and metals, such as alkaline earth metals, titanium, zirconium, iron, cobalt, nickel, copper, zinc, and aluminum; montanic acid lubricants, such as partially saponified montanic acid ester; acrylic lubricants; and silicone oils. These may be used alone or in combination of two or more.

[0041] The lubricant is preferably added in an emulsion state during production of the rubber-reinforced styrene-based resin powder from the viewpoint of uniform dispersion of the lubricant in the powder.

[0042] There is no particular restriction on the timing of adding the emulsion-state lubricant, and examples of the method include (1) mixing it with the rubber-reinforced styrene-based resin latex before powderization, (2) adding it to a slurry of the rubber-reinforced styrene-based resin latex that has been solidified, etc. Among these, the method (1) is preferred from the viewpoint of surface appearance.

[0043] The thermoplastic resin composition of the present invention may contain, in addition to the rubber-reinforced styrene-based resin powder, one or a combination of two or more of other resins, such as acrylic resins such as polymethyl methacrylate; polyolefin-based resins such as polyethylene and polypropylene; polycarbonate resins; polyester-based resins such as polybutylene terephthalate resin, polyethylene terephthalate resin, and polylactic acid resin; polyamide resins; and polyimide-based resins.

[0044] Furthermore, within the scope of the present invention, it is also possible to add hindered amine-based light stabilizers, antioxidants such as hindered phenol-based, sulfur-containing organic compound-based, and phosphorus-containing organic compound-based, heat stabilizers such as phenol-based and acrylate-based, ultraviolet absorbers such as benzoates, benzotriazoles, benzophenones, and salicylates, lubricants such as organic nickel-based and higher fatty acid amides, plasticizers such as phosphoric esters, flame retardants and flame retardant assistants such as polybromophenyl ether, tetrabromobisphenol-A, brominated epoxy oligomers, halogen-containing compounds such as brominated compounds, phosphorus compounds, and antimony trioxide, odor masking agents, pigments such as carbon black and titanium oxide, dyes, etc. Furthermore, it is also possible to add reinforcing agents and fillers such as talc, calcium carbonate, aluminum hydroxide, glass fiber, glass flakes, glass beads, glass wool, carbon fiber, and metal fiber.

[0045] The thermoplastic resin composition of the present invention has a melt volume rate (220°C, 10 kg) of 20 (cm 3 / 10 minutes) or more, and 35 (cm 3 / 10 minutes) or more, and 45 (cm 3 / 10 minutes) or more. 3 / 10 minutes) or less, and 70 (cm 3 By adjusting the viscosity to within the above range, there is a tendency for the balance of impact resistance, fluidity, and heat resistance to be excellent.

[0046] Furthermore, the thermoplastic resin composition of the present invention preferably satisfies the following formula (i). 5≦X / Y≦250... formula (i) X: Melt volume rate of thermoplastic resin composition (220°C, 10 kg) Y: Lubricant content of the above-mentioned rubber-reinforced styrene-based resin powder The lower limit is more preferably at least 10, and even more preferably at least 50. The upper limit is more preferably at most 200, even more preferably at most 150, and most preferably at most 130. By adjusting the value within the above range, there is a tendency for the balance of impact resistance, fluidity, heat resistance, and surface appearance to be excellent. X / Y indicates that there is a correlation between the melt volume rate of the thermoplastic resin composition and the lubricant content of the rubber-reinforced styrene-based resin powder. For example, when the melt volume rate of the thermoplastic resin composition is designed to be high, the rubber-reinforced styrene-based resin powder must contain a large amount of lubricant.

[0047] The thermoplastic resin composition of the present invention can be obtained by melt-kneading the above-mentioned components. For melt-kneading, a known kneading machine such as a roll, a Banbury mixer, a single-screw extruder, a multi-screw extruder, or a kneader can be used. EXAMPLES

[0048] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited thereto. Note that parts and percentages shown in the examples and comparative examples are based on mass. In each of the examples and comparative examples, various physical properties were measured by the following methods.

[0049] [Impact resistance] Using the pellets obtained in each Example and Comparative Example, various test pieces were molded in accordance with ISO test method 294, and the notched Charpy impact value (NC) was measured at a thickness of 4 mm in accordance with ISO test method 179. Unit: kJ / m2

[0050] [Liquidity] Melt Volume Flow Rate (MVR) The pellets obtained in each of the Examples and Comparative Examples were used to measure the melt volume flow rate under conditions of 220°C and a load of 10 kg in accordance with ISO test method 1133. Unit: cm 3 / 10 minutes

[0051] [Heat resistance] Using the pellets obtained in each of the Examples and Comparative Examples, various test pieces were molded in accordance with ISO Test Method 294, and the deflection temperature under load (HDT) at a load of 1.8 MPa was measured in accordance with ISO Test Method 75. Unit: °C

[0052] [Surface appearance evaluation] 40 g of the pellets obtained in each of the Examples and Comparative Examples were used and subjected to a hot press at 230° C. to prepare a film test piece having a thickness of 0.1 mm or less. Three 9 mm diameter circles were drawn at random locations on the obtained test piece, and the number of bumps with a diameter of 50 μm or more within each circle was counted using an optical microscope and the average value was calculated.The number of bumps was then converted into the number equivalent to a 10 cm diameter circle, and the surface appearance was evaluated according to the following criteria. ○: The number of particles larger than 50 μm is less than 550. △: The number of particles larger than 50 μm is between 550 and 800. ×: More than 800 particles larger than 50 μm.

[0053] <Production of graft copolymer latex> A glass reactor was charged with 65 parts by mass of coagulated and thickened styrene-butadiene rubber latex (styrene 5% by mass, butadiene 95% by mass, mass average particle size 440 nm) in terms of solid content, stirring was started, and nitrogen substitution was performed. After nitrogen substitution, the temperature in the tank was raised to 65°C, and an aqueous solution in which 0.06 parts by mass of glucose, 0.03 parts by mass of anhydrous sodium pyrophosphate, and 0.001 parts by mass of ferrous sulfate were dissolved in 10 parts by mass of deionized water was added, and the temperature was then raised to 70°C. Then, a mixture of 10 parts by mass of acrylonitrile, 25 parts by mass of styrene, 0.3 parts by mass of tertiary decyl mercaptan, and 0.1 parts by mass of t-butyl hydroperoxide and an emulsifier aqueous solution in which 1.0 parts by mass of potassium oleate (solid content equivalent) was dissolved in 20 parts by mass of deionized water were continuously dropped over 4 hours. After dropping, the mixture was held for 3 hours to obtain a graft copolymer latex. The graft ratio of the resulting graft copolymer latex was 42%, and the reduced viscosity of the acetone soluble portion was 0.28 dl / g. The mass average particle size of the aggregated and thickened styrene-butadiene rubber latex was determined as follows. The samples were stained with osmium tetroxide (OsO4), dried, and photographed with a transmission electron microscope. The area of ​​800 rubber particles was measured using an image analysis processing device (device name: Asahi Kasei Corporation IP-1000PC), and their circle equivalent diameters (diameters) were calculated to calculate the mass average particle diameter. <Production of rubber-reinforced styrene-based resin powder (A-1)> An emulsion of ethylene bisstearic acid amide was used as the lubricant. (Process 1) 0.39 parts by mass of an emulsion of ethylene bisstearic acid amide (solid content equivalent) was added to 100 parts by mass (solid content equivalent) of the above graft copolymer latex, and mixed. (Process 2) A stirring tank was charged with deionized water so that the final slurry concentration was 25%, and 5 parts by mass of magnesium sulfate was further added thereto. Stirring was started and the temperature inside the tank was raised to 75°C. (Step 3) After the temperature in the tank reached 75°C, the entire amount of the mixture obtained in (Step 1) was added. (Step 4) Thereafter, the obtained coagulated slurry was dehydrated and dried to obtain a rubber-reinforced styrene-based resin powder (A-1).

[0054] <Production of rubber-reinforced styrene-based resin powder (A-2)> The rubber-reinforced styrene-based resin powder (A-1) was produced in the same manner as in the production of the rubber-reinforced styrene-based resin powder (A-1), except that the amount of ethylene bisstearic acid amide emulsion (solid content equivalent) added in (step 1) was changed from 0.39 parts by mass to 0.48 parts by mass. <Production of rubber-reinforced styrene-based resin powder (A-3)> The rubber-reinforced styrene-based resin powder (A-1) was produced in the same manner as in the production of the rubber-reinforced styrene-based resin powder (A-1), except that the amount of ethylene bisstearic acid amide emulsion (solid content equivalent) added in (step 1) was changed from 0.39 parts by mass to 0.67 parts by mass. <Production of rubber-reinforced styrene-based resin powder (A-4)> The rubber-reinforced styrene-based resin powder (A-1) was produced in the same manner as in the production of the rubber-reinforced styrene-based resin powder (A-1), except that the amount of ethylene bisstearic acid amide emulsion (solid content equivalent) added in (step 1) was changed from 0.39 parts by mass to 0.95 parts by mass. <Production of rubber-reinforced styrene-based resin powder (A-5)> The rubber-reinforced styrene-based resin powder (A-1) was produced in the same manner as in the production of the rubber-reinforced styrene-based resin powder (A-1), except that the amount of ethylene bisstearic acid amide emulsion (solid content equivalent) added in (step 1) was changed from 0.39 parts by mass to 10.00 parts by mass. <Production of rubber-reinforced styrene-based resin powder (A-6)> The rubber-reinforced styrene-based resin powder (A-1) was produced in the same manner as in the production of the rubber-reinforced styrene-based resin powder (A-1), except that the amount of ethylene bisstearic acid amide emulsion (solid content equivalent) added in (step 1) was changed from 0.39 parts by mass to 20.00 parts by mass. <Production of rubber-reinforced styrene-based resin powder (A-7)> The rubber-reinforced styrene-based resin powder (A-1) was produced in the same manner as in the production of the rubber-reinforced styrene-based resin powder (A-1), except that the amount of ethylene bisstearic acid amide emulsion (solid content equivalent) added in (step 1) was changed from 0.39 parts by mass to 0 parts by mass. <Production of rubber-reinforced styrene-based resin powder (A-8)> The rubber-reinforced styrene-based resin powder (A-1) was produced in the same manner as in the production of the rubber-reinforced styrene-based resin powder (A-1), except that the amount of ethylene bisstearic acid amide emulsion (solid content equivalent) added in (step 1) was changed from 0.39 parts by mass to 0.19 parts by mass.

[0055] <Production of Polymer (B-1)> A polymer (B-1) consisting of 75 parts by mass of styrene and 25 parts by mass of acrylonitrile was obtained by a known bulk polymerization method. The reduced viscosity of the polymer (B-1) obtained by the above method was 0.44 dl / g. <Production of Polymer (B-2)> A polymer (B-2) consisting of 75 parts by mass of styrene and 25 parts by mass of acrylonitrile was obtained by a known bulk polymerization method. The reduced viscosity of the polymer (B-2) obtained by the above method was 0.62 dl / g. <Production of Polymer (B-3)> A polymer (B-3) consisting of 75 parts by mass of styrene and 25 parts by mass of acrylonitrile was obtained by a known emulsion polymerization method. The reduced viscosity of the polymer (B-3) obtained by the above method was 1.20 dl / g.

[0056] <Other additives> Ethylenebisstearic acid amide (EBS): Kao Wax EB-P manufactured by Kao Corporation

[0057] Examples 1 to 6 and Comparative Examples 1 to 5 The rubber-reinforced styrene-based resin powder (A), polymer (B) and other additives were mixed in the proportions shown in Table 1, and then melt-kneaded and pelletized in a φ26 mm twin-screw extruder with a cylinder temperature of 230° C. and a main screw rotation speed of 300 rpm and a discharge rate of 25 kg / hr. The pellets obtained were used to carry out various evaluations. The results are shown in Table 1.

[0058] [Table 1]

[0059] As is clear from Table 1, the thermoplastic resin composition of the present invention had an excellent balance of impact resistance, fluidity, heat resistance and surface appearance. Comparative Examples 1 and 2 have good impact resistance, heat resistance, and surface appearance, but the MVR is 20 (cm 3 / 10 minutes) and had poor fluidity. Comparative Examples 3 to 5 have good impact resistance and heat resistance, and the MVR is 20 (cm 3 / 10 minutes) or more, the fluidity was good, but the lubricant content of the rubber-reinforced styrene-based resin powder was less than 0.2 parts by mass, and the surface appearance was poor. [Industrial Applicability]

[0060] As described above, the thermoplastic resin composition of the present invention has an excellent balance of impact resistance, fluidity, heat resistance and surface appearance, and therefore can be used in a wide variety of applications, such as vehicle parts, electronic and electrical parts, and housing equipment parts, and is particularly suitable as a material for large molded parts.

Claims

1. A thermoplastic resin composition containing a rubber-reinforced styrene-based resin powder, which satisfies the following conditions (1) and (2): (1) The rubber-reinforced styrene-based resin powder contains 0.2 parts by mass or more of a lubricant per 100 parts by mass of the rubber-reinforced styrene-based resin component. (2) The melt volume rate (220°C, 10 kg) of the thermoplastic resin composition is 20 (cm 3 / 10 minutes) or more.

2. 2. The thermoplastic resin composition according to claim 1, further satisfying the following condition (3): (3) The following formula (i) is satisfied: 5≦X / Y≦250... Formula (i) X: Melt volume rate of thermoplastic resin composition (220°C, 10 kg) Y: Lubricant content of rubber-reinforced styrene-based resin powder

3. A rubber-reinforced styrene-based resin latex is mixed with 0.2 parts by mass or more (solid content equivalent) of an emulsion-state lubricant to 100 parts by mass (solid content equivalent), and then the mixture containing the powdered rubber-reinforced styrene-based resin powder is melt-kneaded to obtain a melt volume rate (220°C, 10 kg) of 20 (cm 3 / 10 minutes) or more.

4. The method for producing a thermoplastic resin composition according to claim 3, further comprising satisfying the following formula (i): 5≦X / Y≦250... Formula (i) X: Melt volume rate of thermoplastic resin composition (220°C, 10 kg) Y: Lubricant content of rubber-reinforced styrene-based resin powder

Citation Information

Patent Citations

  • Production of rubber-reinforced styrene resin

    JP1997316279A

  • Thermoplastic resin composition and its production

    JP1998273578A

  • Production of graft copolymer excellent in impact resistance

    JP2001011138A

  • Thermoplastic resin composition

    JP2002128984A

  • Thermoplastic resin composition

    JP2016188293A